2022
DOI: 10.1177/13524585221114007
|View full text |Cite
|
Sign up to set email alerts
|

Towards a validated definition of the clinical transition to secondary progressive multiple sclerosis: A study from the Italian MS Register

Abstract: Background: Definitions for reliable identification of transition from relapsing-remitting multiple sclerosis (MS) to secondary progressive (SP)MS in clinical cohorts are not available. Objectives: To compare diagnostic performances of two different data-driven SPMS definitions. Methods: Data-driven SPMS definitions based on a version of Lorscheider’s algorithm (DDA) and on the EXPAND trial inclusion criteria were compared, using the neurologist’s definition (ND) as gold standard, in terms of sensitivity, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A recent study from the I-MS&RD Register investigated the contribution of relapse-associated worsening and PIRA to confirmed disability accumulation in patients with clinically isolated syndrome and Relapsing Remitting MS [27]. The use of the Register data also allows to analyze and trace the path of the evolution of disability over time [38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the I-MS&RD Register investigated the contribution of relapse-associated worsening and PIRA to confirmed disability accumulation in patients with clinically isolated syndrome and Relapsing Remitting MS [27]. The use of the Register data also allows to analyze and trace the path of the evolution of disability over time [38].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that prescribing high efficacy drugs early in the history of the disease represents a prominent strategy with the most favorable cost–benefit ratio. This is even more clear if we consider that clinical relapses are only the tip of the iceberg in terms of MS disease activity ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with the current literature. Recent observational studies showed that early initiation of second-line treatment in RR-MS may provide more benefit that an escalation approach in both decreasing the risk of developing secondary progression and disability accrual, at least in terms of a 5-6 years of follow-up (14)(15)(16). This is even more evident when one considers that patients who receive second-line drugs from the beginning are generally those with worst prognostic factors (2,17).…”
Section: Discussionmentioning
confidence: 99%
“…Application of each of the three objective classifiers increased the proportion in all registries as shown in Figure 2(a) for the different methods in each country and in total. Overall, the proportion of SPMS increased using objective classifiers: from 17.7% clinical assignment, 20.1% by EXPAND criteria, 21.8% by the MSBase algorithm, to 28.1% (17,402) according to the decision tree method.…”
Section: Proportion Of Spmsmentioning
confidence: 99%
“…14 It has also previously been applied in a study regarding risk factors in SPMS, 15 in a study to identify RRMS patients at risk for SPMS, 16 and in a comparison with the performance of the neurologist's definition of SPMS. 17 However, since this algorithm requires three visits to establish a conversion, many patient files in registries lack enough documentation to allow classification. The need for a simpler yet accurate approach recently resulted in the development of a decision tree-based classifier that only relies on age and one EDSS score.…”
Section: Introductionmentioning
confidence: 99%